Research on fatigue life calculation method of droppers in high-speed railway catenary - Kou, Hongbo; Yao, Yongming; Lu, Haoshu; Ma, Yunqian (Sound & Vibration, 2026)
To address the problems that catenary droppers are prone to fatigue failure under the operating environment of high-speed trains and are faced with the shortage of load measurement samples, insufficient extrapolation accuracy, and large dispersion in life evaluation, an optimized fatigue load extrapolation method based on small multiples and multiple iterations is proposed. Firstly, a pantograph-catenary coupling system model is established. After verification, the load-time history of the dropper is obtained through dynamic simulation. Secondly, the rainflow counting method is used to statistically analyze the stress cycles. The bandwidth and range of non-parametric rainflow extrapolation are determined according to the extrapolation multiple, and the reliable load extrapolation to the target multiple is realized through a multi-iteration strategy, which is compared with the traditional amplification method and the large-multiple direct extrapolation method. Finally, the mean stress is corrected based on the Goodman model, and a standard fatigue load spectrum is constructed. Combined with the S-N curve and linear cumulative damage theory, a fatigue life prediction model for high-speed railway droppers is established. This study provides a theoretical basis and data support for life evaluation, maintenance schedule formulation, and reliability design of catenary droppers.